Caring for a child with cancer during COVID-19 pandemic: an assessment of the parents’ perception and stress level - Nawi, Muhamad Aizat; Lau, Sie Chong Doris; Chin, Shi Tying; Teh, Kok Hoi; Ho, Lee Sue Betty; Alias, Hamidah (Frontiers in Public Health, 2024)
Background: The emergence of COVID-19 pandemic has led to heightened fear and uncertainty among parents of children with cancer. This study was conducted to evaluate the parental perceptions toward effects of COVID-19 infection to children with cancer, determine their stress level and factors contributing to high stress level during the pandemic. Methods: This cross-sectional study was conducted in three paediatric oncology centres in Malaysia from September 2020 until December 2022. A total of 167 parents were recruited. Parents completed a set of questionnaires to assess their perception on effect of COVID-19 infection to children with cancer and COVID Stress Scale (CSS) to assess the parents’ stress level. Results: Patients’ mean age at study entry was 8.75 years (SD 4.38). Ninety-one (54.5%) patients were still on active treatment. More than 80% of the parents obtained information regarding COVID-19 infection from mass media and social networking. Fear of their children contracting COVID-19 infection was high especially among patients who were still on treatment. Forty-nine (29.3%) parents were significantly affected by the pandemic leading to loss of job or monthly income. Twenty-nine (17.4%) patients required treatment modification during the pandemic. The median total score for CSS was 78.0 (IQR 25th 64.0; 75th 95.0). Ninety-one (54.5%) respondents were very/extremely stressed based on the CSS scores. Components with high scores were xenophobia (median score 18.0; IQR 25th 13.0, 75th 22.0), fear of danger (median score 17.0; IQR 25th 14.0, 75th 20.0) and contamination fears (median score 16.0; IQR 25th 12.0, 75th 19.0). Lower household income was associated with higher stress level (p=0.006). Conclusions: Our study demonstrated high awareness regarding risk of COVID-19 infection among parents of oncology children. Half of the parents had high stress level, with low household income identified as a factor associated with high stress level.